METHODOLOGICAL FOUNDATIONS OF THE MANAGEMENT OF PHYSICAL CULTURE AND SPORTS ACTIVITIES OF STUDENTS IN ORDER TO PREPARE FOR PROFESSIONAL ACTIVITY (Proceedings of International Educators Conference, 2023)
Many experts recognize the need to fundamentally improve the system of physical education of students of secondary and higher educational institutions, aimed at preparing future specialists to pass standards for physical fitness. The lack of students' awareness of the connection of the taught subject with professional training reduces the interest of future teachers in this academic discipline. In addition, students have a natural decrease in interest in physical culture, since they do not receive self-education and self-development skills in this area of upcoming professional activity.